2015
DOI: 10.1021/acs.jpcc.5b05222
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hole Transport between Dyes in Solid-State Dye-Sensitized Solar Cells

Abstract: In dye-sensitized solar cells (DSSCs) photo-generated positive charges are normally considered to be carried away from the dyes by a separate phase of hole transporting material (HTM). We show that there can also be significant transport within the dye monolayer itself before the hole reaches the HTM. We quantify the fraction of dye regeneration in solid state DSSCs that can be attributed to this process. By using cyclic voltammetry and transient anisotropy spectroscopy we demonstrate that the rate of inter-dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…The inter-molecular electrostatic energy of this interaction is -8.72 kcal/mol, which further confirms the evidence of charge transferring between HTM and N3. It is well-known from the literature that a good amount of this type of dye work as donor-π-electrons -acceptor where a large orbital density of the LUMO should cover the carboxylic anchoring groups and a small electronic cloud density cover their HOMO [11][12][13][14][15][16]53]. This similar type of phenomenon is observed in the molecular orbitals of N3 (Fig.S5) which is consistent with the already reported work [11][12][13][14][15][16]53].…”
Section: Polaron and Exciton Binding Energy Of Htmsupporting
confidence: 90%
See 2 more Smart Citations
“…The inter-molecular electrostatic energy of this interaction is -8.72 kcal/mol, which further confirms the evidence of charge transferring between HTM and N3. It is well-known from the literature that a good amount of this type of dye work as donor-π-electrons -acceptor where a large orbital density of the LUMO should cover the carboxylic anchoring groups and a small electronic cloud density cover their HOMO [11][12][13][14][15][16]53]. This similar type of phenomenon is observed in the molecular orbitals of N3 (Fig.S5) which is consistent with the already reported work [11][12][13][14][15][16]53].…”
Section: Polaron and Exciton Binding Energy Of Htmsupporting
confidence: 90%
“…It is well-known from the literature that a good amount of this type of dye work as donor-π-electrons -acceptor where a large orbital density of the LUMO should cover the carboxylic anchoring groups and a small electronic cloud density cover their HOMO [11][12][13][14][15][16]53]. This similar type of phenomenon is observed in the molecular orbitals of N3 (Fig.S5) which is consistent with the already reported work [11][12][13][14][15][16]53]. The higher electronic cloud density at LUMO compared to that of HOMO shows that the charge injection is favored from HTM to dye and prevents charge recombination in the dye molecule.…”
Section: Polaron and Exciton Binding Energy Of Htmmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown that overall device performance of TiO2 / polymer solar cells can be enhanced by more than a factor of two using a self-assembled monolayer 23 on TiO2 nanoparticles with permanent dipole pointing towards the TiO2 surface or pointing towards polymer when compared to a control device with no interface modifiers. It has also been demonstrated that inter dye hole-transport 24,25,26 may contribute to current collection in solid-state dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to these functions, lateral hole diffusion can occur in the dye monolayer by charge transfer between molecules anchored to adjacent sites on the TiO 2 surface11121314151617181920. These interesting phenomena have been shown to improve the performance of solid state DSSCs2122, and may play a role in recombination within liquid DSSCs and devices for water splitting23. Indeed, DSSCs can work without a separate hole transporting phase, with holes being collected solely via the dye monolayer18.…”
mentioning
confidence: 99%